Assessment of selected heavy metal load and identification of bacterial status associated with suya meat sold in Anambra state, Nigeria - N. Asomugha, R.; E. Ilodigwe, E.; O. Amedu, J.; Ogbonnaya, M.; Ifediba, E. (International Journal of Pharmacology and Toxicology, 2021)
Heavy metals and some pathogenic bacteria tend to contaminate food substances commonly consumed and this pose as health risks to the populace. The study was therefore conducted to assess the level of metal and bacteria contamination of meat barbecue (SUYA) commonly consumed in Anambra State, Nigeria. Thirty six sample were evenly collected from the sensational Zones and analyzed using Atomic Absorption Spectrophotometer. Metal values obtained range as follows: Cadmium(4.17-7.93mg/kg), Lead(0.24-3.39mg/kg),Zinc(2.6-28.3mg/kg) and Arsenic(0.19-2.3mg/kg). Samples from Anambra North had the highest Zinc, Lead, and Arsenic levels 14.02, 0.94, and 0.96mg/kg rewspectively, while Anambra South recorded the highest cadmium level 6.16mg/kg. The Estimated daily intake(EDI) of Cadmium alone was found to be greater than the recommended value in the 3 senatorial zones. Again only Cadmium had a target hazard quotient(THQ) of greater than one in all the senatorial zones. All the zones had hazard index (HI) greater than one. North(5.95+00). South,(8.1E+00) and Central(4.8+00). Cancer risk for cadmium recorded in all the zones were above accepted limits. While for Arsenic the North zone recorded levels above acceptable limits. The following bacteria species were isolated from analyze soya samples. Staphyloccocus cereus, Bacillus aureus, Salmonella species, Pseudomonas aeruginosa, Klebsiella pneumonia,however bacillus cereus was most commonly isolated and Pseudomonas aeruginosa least commonly isolated. The results indicated an appreciable level of contamination and a possible public health risk.Â Â
Keywords: Heavy Metals; Bacterial Load; Suya; Cancer Risk.